Specifičnosti bimodalno bilingvalne komunikacije - Šešum, Mia; Šestić , Marina (Specijalna edukacija i rehabilitacija, 2025)
Introduction. Bimodal bilingualism is a special linguistic phenomenon that refers to the mastery of both signed and spoken language. In contrast to unimodal bilingualism, bimodal bilinguals have the ability to use two languages simultaneously. In addition to deaf people, bimodal bilinguals primarily include hearing children of deaf parents and people with cochlear implants. Aim. The aim of this paper is to provide an overview of the characteristics of bimodal bilingualism based on an analysis of contemporary literature, as well as to provide an insight into the linguistic development of bimodal bilinguals and the advantages of this form of communication. Methods. Relevant electronic databases on the Internet were used for the literature research. Results. Bimodal bilingualism is one of the key aspects of a person’s identity. The simultaneous, early acquisition of two languages belonging to different modalities has a positive effect on each of the individual languages. The practical importance of bimodal bilingualism is great for both deaf and hearing people, as it provides them with a common language code and the efficiency of two-way communication. Conclusion. The study of bimodal bilingualism contributes to the affirmation and understanding of deaf and hearing people from deaf families. The positive effects of bimodality on the language development of deaf people show that research in this area needs to be encouraged.
Keywords: bimodal bilingualism; deaf; cochlear implant; communication; children